Analisis Kuat Lekat Angkur Pada Beton Berdasarkan Variasi Bentuk Angkur Dengan Menggunakan Metode Pemasangan Cast In Place: Studi Penelitian - Nur Sabrina Rambe; Darlina Tanjung; M Husni Malik Hasibuan; Afdhal Hubbig (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
An anchor is a steel element that is embedded in concrete when it is cast (cast in place) or installed later (post-installed) into concrete that has hardened and is used to distribute loads (tension and shear) acting on the concrete (SNI 2847:2019). The use of anchors in the world of construction is increasingly popular to help connect concrete structures. The installation of anchors has progressed from the initial anchors being installed before casting the concrete (cast in place), progressing to the anchors being installed after the concrete has hardened (post installed) by drilling. By drilling into concrete, installing and removing anchors becomes easier. Installation of cast-in-place anchors is generally used in the design of new construction, while post-installed anchor installation is generally used in old construction for repairs or retrofitting. Anchors have several variations including hed heax, L bolt and J bolt anchor variations, but it is not yet known which anchor variation has a greater bond strength value, what are the results of the comparison of bond strength values ​​for each variation of anchor and what are the differences in the anchor bond strength capacity for each variation? the anchor. With this research, it is hoped that we can find out the bond strength and bond stress values ​​for each variation of anchor so that the comparison of the bond strength of the anchor can answer the differences in capacity of each variation of the anchor as well. Research on the bond strength of anchors based on variations in anchor shape using the cast in place method shows that the bond strength value shown at the highest loading value is the type J anchor variation with an average load of 27,816 kN, the type L anchor variation with an average load of 26,971 kN and variations of the hex head type anchor with an average load of 12.85 kN. It can be concluded that the stress value is directly proportional to the loading value. The greater the loading value, the greater the bond stress value. The highest bond stress value is found in the type J anchor variation with an average bond stress value of 151,397 Mpa, in the L type anchor variation with an average bond stress value of 147,798 Mpa and in the hex head type anchor variation with an average bond stress value of 69.953 Mpa, so the bond stress is directly proportional to the loading value.